(untitled) (International Journal of Engineering and Computer Science, 2018)
Brushless DC Motor is a highly popular motor because of their high reliability; high efficiency , good dynamic response and very low maintenance so Demand for small & highly reliable motors is increasing. In the BLDC motor at low speed controlling the stator phase current is more effective peed but at high speed range ripple in torque reduction is not reliable in conventional technique. The two techniques sinusoidal PWM and Space vector PWM are studied for close-loop speed control of a BLDC Motor. MATLAB/Simulink simulation model is done for SPWM and SVPWM control scheme. The results of simulation shows the advantage of less harmonic distortion and lower switching of SVPWM is better than that of SPWM technique in losses the speed control of BLDC motor.